The Impact of Climate Change on Witch Trials: Myth or Reality? The Example of Royal Prussia in the Sixteenth–Eighteenth Centuries - Wijaczka, Jacek (Kwartalnik Historyczny, 2023)
The early modern period was also a period of a ‘little ice age’. The sudden fluctuations in climatic conditions that occurred at the time greatly impacted the everyday living conditions of all people of Europe. They also affected, though not to the same degree in all European regions, the perception of the activities of alleged witches.